Redescription of the species Hooperella saccopteryx (Brennan and Jones, 1960) (Trombidiformes: Trombiculidae) and first record to Brazil - de Almeida, Beatriz Rocha [UNESP] (2024)
The Neotropical genus Hooperella Vercammen-Grandjean comprises four valid species, which are primarily found as parasites of bats. Currently, only Hooperella vesperuginis has been recorded in Brazil. In this study, we provide a comprehensive redescription of H. saccopteryx, incorporating data from the type series and newly identified specimens. These new specimens were only identified after a thorough examination of the types. We have included measurements of all seven leg segments, the opisthosoma ventral and sternal setae, which were not previously recorded. Notably, we observed differences in the number of specialized setae (σ) on the genu of leg I. Furthermore, this examination marks the first record of H. saccopteryx in Brazil.